COVID-19 and violence: a research call to action - Evans, Dabney P. (BMC Womens Health, 2020)
COVID-19 related guidelines and movement restrictions are designed to protect the public’s health and reduce disease transmission; yet, COVID-19 related restrictions on movement including social distancing, isolation, quarantine, and shelter-in-place orders have an unknown effect on violence and abuse within relationships. As the pandemic has progressed, many have justifiably speculated that such restrictions may pose a danger to the safety and well-being of people experiencing such violence. Early in the pandemic, countries hard hit by COVID-19 began raising the alarm bell about the impacts of the disease on IPV occurrence. Police in China report that 90% of the causes of recent IPV cases could be attributed to the COVID-19 epidemic. Rising fears and anxiety about prolonged movement restrictions, increased economic strain and diminished health care capacity to support survivors are among the potential reasons for such dramatic effects. Under normal circumstances: low income, unemployment, economic stress, depression, emotional insecurity and social isolation are all risk factors for using violence against partners. Many of these factors may worsen in the context of COVID-19. Despite the urgency in addressing COVID-19, existing health concerns like Intimate Partner Violence (IPV) persist—and may well be worsened by the virus. We simply do not yet know the effects of COVID-19 on violence, nor do we know which interventions work best to prevent and respond to it within the context of the pandemic. The vast majority of information available about IPV and violence during the pandemic has been based on anecdotal reports. The call to action for the research community is clear. We must systematically measure the effects of COVID-19 and movement related restrictions on violence. As always when researching violence, serious consideration must be given to ethics and safety. Violence researchers must mobilize to investigate the impacts of COVID-19 on violence and human health.